1987
DOI: 10.1002/aja.1001790109
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic bar‐like structures of alveolar type II cells: An ultrastructural study in freshly isolated cells from rat lungs

Abstract: Bar-like structures are tubular cytoplasmic inclusions found in situ in pulmonary epithelial type II cells of several animal species. The physiological significance and mode of formation of these inclusions are not fully established. In this paper, we describe bar-like structures as found in freshly isolated type II cells from rat lungs. Pulmonary cells were dissociated from the tissue with elastase and separated on a discontinuous density gradient of Percoll. The complete isolation procedure yielded 17 X 10(6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This finding was similar to the plate body of sheep type 2 cells found in the present study, although they did not examine the serial sections of the structures. In rat alveolar type 2 cells, Shimura et al (1980) reported barlike structures for the first time, confirmed later by Vincent and Nadeau (1987). The barlike structures of rat type 2 cells were concentrically arranged tubular cytoplasmic inclusions that contained osmiophilic periodic materials, the periodicity of which was 26 A and the width of which was 0.15 to 0.40 pm.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This finding was similar to the plate body of sheep type 2 cells found in the present study, although they did not examine the serial sections of the structures. In rat alveolar type 2 cells, Shimura et al (1980) reported barlike structures for the first time, confirmed later by Vincent and Nadeau (1987). The barlike structures of rat type 2 cells were concentrically arranged tubular cytoplasmic inclusions that contained osmiophilic periodic materials, the periodicity of which was 26 A and the width of which was 0.15 to 0.40 pm.…”
Section: Discussionmentioning
confidence: 84%
“…These findings were consistent with previous reports on the barlike structures in rats (Shimura et al, 1980(Shimura et al, , 1985Vincent and Nadeau, 19861, filamentary tubular inclusions in guinea pigs (Manabe and Ikeda, 19861, rod-shaped structures in dogs (Stephens et al, 19731, and the cisternal bodies in ferrets (Miller et a1.,1982). More recently, Vincent and Nadeau (1987) demonstrated that the barlike structures of rat type 2 cells can be bound to virtually any of the intracellular membrane systems: the Golgi apparatus, the rough endoplasmic reticulum, and the nuclear membrane. This study has shown that most of the plate bodies were connected to each other and to the cisternal body, in addition to the rough endoplasmic reticulum, but no direct continuation with the Golgi apparatus or the nuclear membrane was found.…”
Section: Discussionmentioning
confidence: 99%
“…tubular inclusions bounded by/associated with ER, and containing a cytoplasmic core and more or less concentrically arranged osmiophilic lamellae. These structures have been observed in type II cells isolated from the rat lung (Vincent and Nadeau 1987), and in rat type II cells studied in situ after stimulation with cholinergic agents like pilocarpine (Shimura et al 1985), as well as in type II cells in several other animal species (see Shimura et al 1985;Vincent and Nadeau 1987). It is possible to imagine that in certain (stimulated) conditions lamellae formation takes place not only in more or less globular forms of secluded cytoplasm, but also in other (e.g.…”
Section: Discussionmentioning
confidence: 99%